Tailoring Theoretical Lens and Nudging Bourdieu’s Cultural Capital on Gender and Academic Performance (Journal of Social Sciences Review, 2024)
This paper has been designed to analyze theoretical insights into gender-based academic performance in higher education through the lens of Bourdieu's cultural capital theory. A systematic approach to review the published and available documents in online databases. The researcher reaches the point of saturation by browsing 68 published documents. These documents have been selected using the inclusion criteria on gender differentials in academic performance in higher education. The study findings outline that biological differences are less likely to affect the performance of female and male students rather than shaped by cultural differences. Females’ deprivation of education was due to the traditional and cultural practices in male hegemonic society. The study concludes that the difference in educational performance among female and male students in higher education is not linked with biological characteristics. It has roots in the difference of psycho-social, socio-economic, and cultural factors of socialization among female and male students.
Keywords: Gender; Academic Performance; Cultural Capital; Higher Education; Sociology